The Leontief and Schultz Methods of Deriving "Demand" Curves - Gilboy, Elizabeth Waterman (Quarterly Journal of Economics, 1931)
I. The technique of the Schultz and Leontief methods, 219. — II. The logic of the methods, 223. — III. Application of both methods to price-quantity data for coffee, 232; copper, 237; sugar, 240. — IV. English import and export indexes, 242. — V. Comparison of the results of these experiments, 253. — VI. Criticism of the Leontief and Schultz logic, 255. — Conclusion, 260.